2020
DOI: 10.3390/diagnostics10100821
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Structure Models in the Evaluation of Novel Variant (C.472_477del) in the MOCS2 Gene

Abstract: (1) Background: Molybdenum cofactor deficiency type B (MOCODB, #252160) is a rare autosomal recessive metabolic disorder characterized by intractable seizures of neonatal-onset, muscular spasticity, accompanying with hypouricemia, elevated urinary sulfite levels and craniofacial dysmorphism. Thirty-five patients were reported to date. (2) Methods: Our paper aimed to delineate the disease genotype by presenting another patient, in whom a novel, in-frame variant within the MOCS2 gene was identified. (3) Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…To date, 39 MOCD-B patients with 33 different MOCS2 gene variants have been reported, 4 , 5 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 including this one reported in our study. We reviewed the detail clinical and genetic data of each patient and verified the variants carefully.…”
Section: Discussionsupporting
confidence: 50%
“…To date, 39 MOCD-B patients with 33 different MOCS2 gene variants have been reported, 4 , 5 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 including this one reported in our study. We reviewed the detail clinical and genetic data of each patient and verified the variants carefully.…”
Section: Discussionsupporting
confidence: 50%
“…The c.471_477delTTTAAAAinsG variant of the Mocs2 protein has not been reported in the ExAC ( (accessed on 10 March 2023)) or gnomAD ( (accessed on 10 March 2023)) databases. However, the previously described c.472_477del variant [ 5 ] is present in both databases and has a frequency of 1.19 × 10 −5 in gnomAD v.2.1.1 and 1.65 × 10 −5 in ExAC v.1.0. Both of these mutations do not cause a frameshift and result in the same deletion of two amino acids (Leu158 and Lys159) in the protein product (p.Leu158_Lys159del).…”
Section: Resultsmentioning
confidence: 97%
“…The structure analysis indicated that residues Leu158 and Lys159 are located at the end of the last helix and are involved in the binding of MPT synthase small subunits. Thus, the heterodimer and active complex formation were impaired in this variant [ 68 ]. In conclusion, these studies demonstrate a link between residual Moco synthesis activity and delayed onset and/or a milder course of the disease.…”
Section: Genetics Of Moco Deficiencymentioning
confidence: 99%